The market valuation of cash dividends - Poterba, James M (Journal of Financial Economics, 1986)
This paper re-examines the case of Citizens Utilities, a firm with one class of common stock which pays stock dividends and one which pays taxable cash dividends. John Long's (1978) study of the two shares' relative prices suggests that investors may prefer cash dividends to equal-sized stock dividends. This paper finds that the cash dividend share's ex-day price decline is less than their dividend payment. Stock dividend shares fall by nearly their full dividend. The disparity between ex-day dividend valuation and the observed prices of the two shares is inconsistent with some explanations of the demand for cash dividends.